2015
DOI: 10.1248/bpb.b15-00133
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Study of L-Glutamate and L-Glutamine Transport in Retinal Pericytes: Involvement of Excitatory Amino Acid Transporter 1 and Alanine–Serine–Cysteine Transporter 2

Abstract: L-Glutamate (L-Glu) is known to be a relaxant of pericytes and to induce changes in microcirculatory hemodynamics. Since the concentration of L-Glu which induces the dilation of retinal capillaries is reported to be high compared with the estimated concentration in the retinal interstitial fluid, it is hypothesized that some systems involving concentrative L-Glu release are present in retinal pericytes. The purpose of this study was to investigate the existence of L-Glu-storing systems, which contribute to aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Subsequently, the glutamate may be extruded across the luminal membrane into the bloodstream through another type of glutamate carrier, referred to as facilitative glutamate transporters (Hawkins and Viña, 2016). Finally, at least one study, performed in the retina, described an EAAT-mediated glutamate uptake by another brain cell type-pericytes (Akanuma et al, 2015). A scheme summarizing the mechanism of glutamate uptake in the ischemic CNS is shown in Figure 3.…”
Section: Glutamate Transportersmentioning
confidence: 99%
“…Subsequently, the glutamate may be extruded across the luminal membrane into the bloodstream through another type of glutamate carrier, referred to as facilitative glutamate transporters (Hawkins and Viña, 2016). Finally, at least one study, performed in the retina, described an EAAT-mediated glutamate uptake by another brain cell type-pericytes (Akanuma et al, 2015). A scheme summarizing the mechanism of glutamate uptake in the ischemic CNS is shown in Figure 3.…”
Section: Glutamate Transportersmentioning
confidence: 99%
“…The transport process involves the uptake of one molecule of glutamate, three Na + , and one H + into astrocytes, while simultaneously exporting one K + from astrocytes 19,20 . Research has indicated that the Km values for glutamate transport into astrocytes, facilitated by EAAT1 and EAAT2 in rats, are 11 and 17 μM, respectively 21 …”
Section: Glutamate–glutamine Cyclementioning
confidence: 99%
“…19,20 Research has indicated that the Km values for glutamate transport into astrocytes, facilitated by EAAT1 and EAAT2 in rats, are 11 and 17 μM, respectively. 21 GLT-1 is considered the major glutamate transporter among astrocytic EAATs. It accounts for approximately 1% of the total brain protein in the CNS and is responsible for more than 90% of glutamate uptake.…”
Section: Glutamate Uptake By Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation